Degradação de carbendazim em água por foto-Fenton solar em um fotorreator semipiloto do tipo RPR - Elizangela Pinheiro da Costa (2017)
In Brazil, the fungicide carbendazim is a pesticide of special concern due to its high sales rate (15th in number of sales on 2014), as well for some of its characteristics such as toxicity, mutagenicity and development and reproductive effects. Carbendazim has been detected in different water matrices around the world, including surface and groundwater, potable water and treated sewage. Therefore, it is not efficiently removed by conventional water and wastewater treatments. On the other hand, advanced oxidation processes (AOPs), such as photocatalysis, ozonation and H2O2/UV system, have shown high degradation rates and elevated toxicity removal of carbendazim contaminated water. In this way, this work aims the degradation of carbendazim by solar photo-Fenton in a new model of photoreactor, the Raceway Pond Reactor (RPR). Initial experimentation included the treatment of carbendazim by different AOPs and two set of irradiation sources (UV: ë > 254nm and UV-Vis: ë > 315nm). Fenton and foto-Fenton (UV and UV-Vis) processes achieved high degradation efficiency (> 93%) at a short amount of time (less than 1 minute), in addition to their excellent removal of acute toxicity. On the other hand, UV photolysis and H2O2/UV-Vis systems achieved such high efficiencies at longer reaction time (40 60 minutes) and showed increase on the final acute toxicity of the solution. The H2O2/UV system also resulted in a high degradation efficiency at longer reaction time (60 minutes), but the final acute toxicity was reduced. The following experiments included variation on the initial concentration of reagents and the water depth of the RPR reactor. As the results indicated very similar carbendazim degradation efficiencies, the next phase of experiments comprised of a complete factorial design 2³, which considered as factors reagents Fe²+ and H2O2 and depth of water. Initial iron concentration was the only significant (á = 5%) factor on carbendazim degradation efficiency. The best carbendazim removal efficiency was achieved on the following condition: 1,5mg.L-¹ Fe²+, 12,5mg.L-¹ H2O2 and 5cm of water depth. This optimized condition of the solar photoFenton achieved more than 93% of carbendazim degradation in 15 minutes of reaction, alongside effective acute toxicity removal and the lowest cost among the studied treatments (0,57R$.m-³).